Z historii zagranicznego ruchu turystycznego w Polsce - Kłysz, Piotr (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2010)
The beginnings of tourist traffic in Poland go back to the second half of the 20th century. Earlier, particularly between 1945–1856, foreign tourism was almost non-existent. Tourism started to develop at the end of that period. The development gained momentum in the first half of the 1960s. In 1955 about 77,000 foreign tourists came to Poland and 44,000 Poles went to other countries. These figures have been growing considerably in the following years – in 1965 778,400 Polish tourists visited other countries and as many as 1,162,900 foreign tourists came to Poland. Foreign tourist traffic has been mainly organized by the Polish Travel Office Orbis. Other institutions involved in the organization of foreign tourism in Poland included PTTK (Polish Tourist and Sightseeing Organization), ZMS (Union of Socialist Youth), ZSP (Union of Polish Students), Polish Tourist Cooperative Gromada, and Turysta Cooperative. The opinions about Polanď’s attractiveness for tourists varied. In the 1980s many foreign tourists believed that Poland is not a very attractive tourist destination. A number of people who visited Poland in recent years have had a completely different opinion. In tourist materials dating back to the beginnings of the 1960s we can read that foreigners find in Poland everything that could be expected from a tourist trip, i.e., beautiful landscapes (Photo 1), and beautiful historical architecture (Photo 2). Polish tourists also go to many attractive regions of the world (Photo 3).
Keywords: Poland; Touristic visits; Goreign tourists